2018
DOI: 10.1159/000489756
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Effects of Suppression of MicroRNA-383 in Human Bone-Marrow-Derived Mesenchymal Stem Cells on Treating Spinal Cord Injury

Abstract: Background/Aims: Transplantation of bone-marrow-derived mesenchymal stem cells (MSCs) promotes neural cell regeneration after spinal cord injury (SCI). Recently, we showed that suppression of microRNA-383 (miR-383) in MSCs increased the protein levels of glial cell line derived neurotrophic factor (GDNF), resulting in improved therapeutic effects on SCI. However, the overall effects of miR-383 suppression in MSCs on SCI therapy were not determined yet. Here, we addressed this question. Methods: We used bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For instance, miR-153-3p [43], miR-383-5p [81] and miR-526b-3p [87] have been reported to target VEGF, while miR-944 targets VEGFC in ECs [100]. Notably, the direct binding of miR-383-5p to VEGF mRNA has been confirmed by Han et al in ECs [137] and demonstrated in other cell types, including bone-marrow-derived mesenchymal stem cells [138] and lung adenocarcinoma cells [139]. Moreover, miR-2355-5p (miR-2355) targets VEGFR2 in ECs [68].…”
Section: Vegf/vegf Receptor (Vegfr) Pathwaymentioning
confidence: 88%
“…For instance, miR-153-3p [43], miR-383-5p [81] and miR-526b-3p [87] have been reported to target VEGF, while miR-944 targets VEGFC in ECs [100]. Notably, the direct binding of miR-383-5p to VEGF mRNA has been confirmed by Han et al in ECs [137] and demonstrated in other cell types, including bone-marrow-derived mesenchymal stem cells [138] and lung adenocarcinoma cells [139]. Moreover, miR-2355-5p (miR-2355) targets VEGFR2 in ECs [68].…”
Section: Vegf/vegf Receptor (Vegfr) Pathwaymentioning
confidence: 88%
“…MiR-383 directly targets VEGFA and has been implicated as a regulator of angiogenesis in the highly vascular central nervous system tumor malignant glioma, with overexpression of miR-383 resulting in profound downregulation of proliferation, migration, and tube formation of cellular models of malignant glioma ( 171 ). Downregulation of miR-383 also resulted in improved angiogenesis in models of spinal cord injury in rats ( 172 ). Han et al ( 173 ) explored the effects of miR-383 in diabetic wound healing by studying its interactions with the long non-coding RNA krüppel-like factor 3 antisense RNA 1 (KLF3-AS1) delivered by BMSC-derived exosomes, and they found that these exosomes promoted increased proliferation, migration, and tube formation in HUVECs grown in high glucose media.…”
Section: Dysregulated Micrornas In Diabetic Angiogenesismentioning
confidence: 99%
“…MiR-383 suppression increased the proliferation of MSCs and MSC-mediated angiogenesis due to the increased expression of CDK-19 and VEGF-A, respectively. The up-regulated expression of CDK19 and VEGF-A further improved the therapeutic potential of MSCs in treating spinal cord injury (SCI) in rats [76].…”
Section: Mir-383 In Development and Cell Differentiationmentioning
confidence: 99%